Degradation of pharmaceutical mixtures in aqueous solutions using UV/peracetic acid process: Kinetics, degradation pathways and comparison with UV/H2O2. (June 2020) - Hollman, Jordan; Dominic, John Albino; Achari, Gopal
Abstract: This paper presents an evaluation of UV/PAA process for degradation of four pharmaceuticals venlafaxine (VEN), sulfamethoxazole (SFX), fluoxetine (FLU) and carbamazepine (CBZ) with comparison to UV/H2 O2 process. The effectiveness of combining PAA and H2 O2 at various proportions while irradiating with UVC were also evaluated. UVC/PAA ( λ  = 254 nm) was effective in degrading all four pharmaceuticals and followed pseudo first-order kinetics. Increasing PAA dosage or UVC intensity resulted in a linear increase in pseudo-first order rate coefficient. Both PAA in dark conditions and UVA/PAA ( λ  = 360 nm) were marginally effective to degrade SFX and ineffective to degrade VEN, CBZ and FLU; indicating the need for UVC irradiation for activation of PAA. For similar oxidant dosages of 50 mg/L UVC/H2 O2 was found to be faster than UV/PAA for VEN, CBZ and FLU by 55%, 75% and 33%, respectively. Under similar conditions, SFX was degraded 24% faster by UV/PAA. Increase in the proportion of H2 O2 to PAA in UVC/PAA/H2 O2 improved kinetics of degradation compared to PAA alone. Tests on TOC were conducted to determine the amount of acetic acid that is released to water when treatment by UVC/PAA is conducted. Results demonstrated that 70% of PAA by mass was ultimately converted to acetic acid and remained in the treated solutions. Hydroxyl radical attack is hypothesized to be the main mechanism of degradation by UV/PAA as degradation intermediates identified for all the target pharmaceuticals coincided with by-products identified during UV/H2 O2 process. Highlights: UV/Peracetic acid effectively degrades recalcitrant pharmaceutical compounds. UV/H2 O2 is more effective than UV/PAA except for sulfamethoxazole. Degradation pathway by UV/PAA is dominated by HO. ● attacks. UV/PAA treatment leads to a significant TOC increase due to release of acetic acid.